Comparison of verbs in Kurdish and Persian (from the perspective of minority programs) - Abubakr Omar Qadir (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
This study tries to shed light on some aspects of similarity of the verb phrase in Kurdish and Persian according to Minimalist Program. The study is compared of two main sections. The first section is specified to present a summary of the program and the application steps in the selection of lexical items along with the numeration of their usage in the computational system in which merging is regarded as a mechanism of expressions. In this program the movement of the items is known as a movement which is divided in to constituent movement and specific constituent movement. The purpose of the latter movement is to express explicitly. This is so, because this method will be a technique to the entire interpretation. This means that the phonological interpretation will reflect the logical form. At the end of this section, the steps of development are presented with examples. The second section is devoted to the study of the structures of verb phrases and a plausible interpretation is given this phrase which is possibly the counter part of V˭ or S. According to minimalist programme the internal VP, which has a lexical head, consists of the VP shell whose head is Ø. This means that big VP is inside the small vp. The verb in VP in the head which needs its complements, that is to say, its complements will be the functional and lexical items. The present study focuses on the head of VP, in which Inflectional Phrase/ I̅ arranges tenses and person. In other words, the emergence of Agr phrase in which T will be the head of T˭. Move over, all the changes within the structure of VP in minimalist programme have been discussed. According to the orientation of the theory and the programme, the structure of sentences and VPs of both Kurdish and Persian Languages are drawn and compared tree diagrams, namely, in the VPs whose head are either transitive or intransitive verbs, passive and active constructions. The sharing point between the languages is identical and parallel. Even though Kurdish is a north-west Iranian language. Persian is a south-western language.